In Vitro Bioaccessibility of the Vitamin B Series from Thermally Processed Leafy African Indigenous Vegetables - Zipporah M. Onyambu; Mildred P. Nawiri; Hudson N. Nyambaka; Naumih M. Noah (Journal of Food Quality)
Thermal processing of leafy African indigenous vegetables (LAIVs), which are rich in nutrients, especially vitamin B series affects the levels and bioaccessibility of the vitamins. This study investigated the bioaccessibility of vitamin B series in fresh and thermally processed LAIVs. Five commonly consumed indigenous vegetables, Cleome gynadra, Vigna unguilata, Amaranthus viridis, Basella alba, and Cucurbita maxima, were processed by boiling and/or frying, treated to in vitro gastrointestinal digestion procedure, and levels of vitamin B series determined before and after treatment. The vitamin B series in fresh LAIVs ranged from 0.73 ± 0.01 mg/100 g (B9; spider plant) to 174.16 ± 3.50 mg/100 g (B2; vine spinach) and had both significant increase (ranging from +8.71% to +446.84%) and decrease (ranging from −0.44% to −100.00%) with thermal processing (p<0.001). The in vitro digestion resulted in a significant increase (p<0.001) of vitamins ranging from 5.18% (B5; boiled cowpeas) to 100% (B2, B3, and B6 in several processed vegetables). Where detected, the bioaccessible levels of vitamin B series in fresh, processed, and in vitro digested samples were sufficient to meet the Recommended Dietary Allowances (RDA) of children and adults. These findings support the promotion of a nutritional approach to malnutrition resulting from vitamin B series deficiency.